2004
DOI: 10.1038/sj.eye.6701476
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of diabetic retinopathy and macular oedema: a systematic review

Abstract: Aims To systematically review the literature on the prevalence and incidence of diabetic retinopathy (DR) and macular oedema (MO). Methods A search of the bibliographic databases (Medline, Embase, CINAHL) was conducted up to October 2001. Selected relevant studies were scrutinized and included in the review. Results A total of 359 studies were included. The studies were reported in nearly 100 different journals and in over 50 countries. The majority of the studies were US-based, with large studies such as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
243
7
31

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 400 publications
(302 citation statements)
references
References 225 publications
13
243
7
31
Order By: Relevance
“…However, in our study, the prevalence was lower than reported in previous studies (Williams et al. 2004). Interestingly, the prevalence of diffuse macular cysts was already higher in individuals with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, in our study, the prevalence was lower than reported in previous studies (Williams et al. 2004). Interestingly, the prevalence of diffuse macular cysts was already higher in individuals with prediabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Es pues muy importante el estricto control de la glicemia en los pacientes diabĂ©ticos como ponen de manifiesto diversos estudios (17,(23)(24)(25). Entre ellos el DCCT (17) que demostrĂł que un estricto control de la glucemia, durante un periodo prolongado, reduce la incidencia de edema macular, con un riesgo relativo de un 0,78, siendo el porcentaje de cambio de -22,1%.…”
Section: Discussionunclassified
“…As there are inconsistencies between epidemiological studies and differences in study methods may contribute to conflicting reports of prevalence and incidence [13], we restricted the search to studies using the reference method for DR diagnosis (e.g. multi-field stereoscopic fundus photography graded by an ophthalmologist using the ETDRS classification [14]).…”
Section: Literature Search Methodsmentioning
confidence: 99%